Effects of acute and chronic administration of neurosteroid dehydroepiandrosterone sulfate on neuronal excitability in mice - Svob Strac D; Vlainic J; Samardzic J; Erhardt J; Krsnik Z (Dove Medical Press, 2016)
Dubravka Svob Strac,1 Josipa Vlainic,1 Janko Samardzic,2 Julija Erhardt,3 Zeljka Krsnik41Laboratory for Molecular Neuropsychiatry, Division of Molecular Medicine, Rudjer Boskovic Institute, Zagreb, Croatia; 2Institute of Pharmacology, Clinical Pharmacology and Toxicology, Medical Faculty, University of Belgrade, Belgrade, Serbia; 3Department of Animal Physiology, Faculty of Science, University of Zagreb, 4Croatian Institute for Brain Research, Department of Neuroscience, School of Medicine, University of Zagreb, Zagreb, CroatiaBackground: Neurosteroid dehydroepiandrosterone sulfate (DHEAS) has been associated with important brain functions, including neuronal survival, memory, and behavior, showing therapeutic potential in various neuropsychiatric and cognitive disorders. However, the antagonistic effects of DHEAS on γ-amino-butyric acidA receptors and its facilitatory action on glutamatergic neurotransmission might lead to enhanced brain excitability and seizures and thus limit DHEAS therapeutic applications. The aim of this study was to investigate possible age and sex differences in the neuronal excitability of the mice following acute and chronic DHEAS administration.Methods: DHEAS was administered intraperitoneally in male and female adult and old mice either acutely or repeatedly once daily for 4 weeks in a 10 mg/kg dose. To investigate the potential proconvulsant properties of DHEAS, we studied the effects of acute and chronic DHEAS treatment on picrotoxin-, pentylentetrazole-, and N-methyl-d-aspartate-induced seizures in mice. The effects of acute and chronic DHEAS administration on the locomotor activity, motor coordination, and body weight of the mice were also studied. We also investigated the effects of DHEAS treatment on [3H]flunitrazepam binding to the mouse brain membranes.Results: DHEAS did not modify the locomotor activity, motor coordination, body weight, and brain [3H]flunitrazepam binding of male and female mice. The results failed to demonstrate significant effects of single- and long-term DHEAS treatment on the convulsive susceptibility in both adult and aged mice of both sexes. However, small but significant changes regarding sex differences in the susceptibility to seizures were observed following DHEAS administration to mice.Conclusion: Although our findings suggest that DHEAS treatment might be safe for various potential therapeutic applications in adult as well as in old age, they also support subtle interaction of DHEAS with male and female hormonal status, which may underline observed sex differences in the relationship between DHEAS and various health outcomes.Keywords: dehydroepiandrosterone sulfate, mice, age and sex differences, seizure threshold, motor activity, [3H]flunitrazepam binding